Odpowiedź :
Odpowiedź:
zastosuj grupowanie
a) W (x) = x³ + 2x² - 4x - 8 = x²(x+2)- 4(x+2)=(x²-4)(x+2)= (x+2)(x-2)(x+2)=
(x+2)²(x-2)
b) W (x) = x³ - 3x² - 4x + 12 = x²(x-3) -4(x-3)=(x²-4)(x-3)= (x+2)(x-2)(x-3)
Szczegółowe wyjaśnienie:
Odpowiedź:
a)
W(x) = x³ + 2x² - 4x - 8
W(x) = x²(x + 2) - 4(x + 2)
W(x) = (x + 2)(x² - 4)
W(x) = (x + 2)(x - 2)(x + 2)
b)
W(x) = x³ - 3x² - 4x + 12
W(x) = x²(x - 3) - 4(x - 3)
W(x) = (x - 3)(x² - 4)
W(x) = (x - 3)(x - 2)(x + 2)
Szczegółowe wyjaśnienie:
Stosuję metodę grupowania wyrazów.
Oraz wzór skróconego mnożenia:
(a - b)(a + b) = a² - b²
a)
W(x) = x³ + 2x² - 4x - 8
W(x) = x²(x + 2) - 4(x + 2)
W(x) = (x + 2)(x² - 4)
W(x) = (x + 2)(x - 2)(x + 2)
b)
W(x) = x³ - 3x² - 4x + 12
W(x) = x²(x - 3) - 4(x - 3)
W(x) = (x - 3)(x² - 4)
W(x) = (x - 3)(x - 2)(x + 2)
Szczegółowe wyjaśnienie:
Stosuję metodę grupowania wyrazów.
Oraz wzór skróconego mnożenia:
(a - b)(a + b) = a² - b²